Epicardium-Derived Cells Formed After Myocardial Injury Display Phagocytic Activity Permitting In Vivo Labeling and Tracking. (7th April 2016) - Ding, Zhaoping; Temme, Sebastian; Quast, Christine; Friebe, Daniela; Jacoby, Christoph; Zanger, Klaus; Bidmon, Hans-Jürgen; Grapentin, Christoph; Schubert, Rolf; Flögel, Ulrich; Schrader, Jürgen
Abstract : Epicardium-derived cells (EPDCs) formed after myocardial infarction can specifically endocytose nanoparticles in vivo and in vitro. This novel feature permitted in vivo targeting of EPDCs with either a perfluorocarbon-containing or rhodamine-conjugated nanoemulsion to track migration and fate decision of EPDC with 19 F-magnetic resonance imaging and fluorescence microscopy. Abstract: : Epicardium-derived cells (EPDCs) cover the heart surface and can function as a source of both progenitor cells and trophic factors for cardiac repair. Currently, EPDCs cannot be conveniently labeled in vivo to permit imaging and cell tracking. EPDCs formed after myocardial infarction (MI) preferentially take up a perfluorocarbon-containing nanoemulsion (PFC-NE; 130 ± 32 nm) injected 3 days after injury, as measured by 19 F-magnetic resonance imaging ( 19 F-MRI). Flow cytometry, immune electron microscopy, and green fluorescent protein (GFP)-transgenic rats (only immune cells, but not epicardial cells, are GFP + ) demonstrated that PFC-containing EPDCs are nonhematopoietic (CD45 - /CD11b - ) but stain positive for markers of mesenchymal stem cells such as platelet-derived growth factor receptor α (PDGFR-α) CD73, CD105, and CD90. When rhodamine-coupled PFC-NE was used, we found that ρ + vessel-like structures formed within the infarcted myocardium, comprising approximately 10% of all large vessels positive for smooth muscle actin (SM-actin). The epicardial cell layer, positive for Wilms' tumor 1 (WT-1), PDGFR-α, or KI-67, was shown to be well capillarized (293 ± 78 capillaries per mm 2 ), including fenestrated endothelium. Freshly isolated EPDCs were positive for WT-1, GATA-4, KI-67, and FLK-1 (75%), PDGFR-α (50%), and SM-actin (28%) and also exhibited a high capacity for nanoparticle and cell debris uptake. This study demonstrates that EPDCs formed after MI display strong endocytic activity to take up i.v.-injected labeled nanoemulsions. This feature permitted in vivo labeling and tracking of EPDCs, demonstrating their role in myo- and vasculogenesis. The newly discovered endocytic activity permits in vivo imaging of EPDCs with 19 F-MRI and may be used for the liposomal delivery of substances to further study their reparative potential. Significance: The present study reports that epicardium-derived cells (EPDCs) formed after myocardial infarction can specifically endocytose nanoparticles in vivo and in vitro. This novel feature permitted in vivo targeting of EPDCs with either a perfluorocarbon-containing or rhodamine-conjugated nanoemulsion to track migration and fate decision of EPDC with 19 F-magnetic resonance imaging and fluorescence microscopy. The liposomal nanoemulsions used in the present study may be useful in the future as a nanomedical device for the delivery of substances to direct cell fate of EPDCs.